Sponsorship effectiveness in professional sport: an examination of recall and recognition among football fans. Issue 1 (1st October 2014) - Biscaia, Rui; Correia, Abel; Ross, Stephen; Rosado, António
Abstract : This research aims to examine football fans' awareness of their team sponsors and to compare sponsorship awareness between season ticket holders and casual spectators. Data was collected from among fans of a professional football team and results revealed that spectators recall 'top of mind' those sponsors with their logo displayed on the team shirts. Thus, being visible from the stadium stands is important to ensure recall rates. Fans are typically able to properly recognise sponsors and non-sponsors of their team. However, some competitor brands engaged in football sponsorship are incorrectly recognised as sponsors of a team. Finally, the number of brands recalled and recognised correctly by season ticket holders is significantly higher than for casual spectators. The research findings, managerial implications, limitations and future research directions are discussed.